Camrelizumab plus gemcitabine and oxaliplatin for the treatment of advanced intrahepatic cholangiocarcinoma: a bi-centric observational retrospective study - Zhang, Yu-Qing; Wang, Kang; Feng, Jin-Kai; Yuan, Lu-Yun; Liang, Chao; Xiang, Yan-Jun; Wang, Xu; Mao, Fei-Fei; Cheng, Shu-Qun (Frontiers in Oncology, 2023)
Background Immune checkpoint inhibitor (ICI), coupled with systemic chemotherapy, may enhance the clinical benefit of cancer by potentiating antitumor immunity, but its efficacy and safety are not clear in advanced intrahepatic cholangiocarcinoma (ICC). This study aims to assess the efficacy and safety of camrelizumab plus gemcitabine and oxaliplatin (GEMOX) for the treatment of advanced ICC in the real world. Methods Advanced ICC patients receiving at least one session of camrelizumab plus GEMOX combination treatment from March 2020 to February 2022 at two high-volume centers were considered eligible. Tumor response was evaluated based on the Response Evaluation Criteria in Solid Tumors version 1.1 (RECIST v1.1). The primary endpoint was objective response rate (ORR), disease control rate (DCR), time to response (TTR), and duration of response (DOR). The secondary end points included overall survival (OS), progression-free survival (PFS), and treatment-related adverse events (TRAEs). Results 30 eligible ICC patients were enro1led and analyzed in this observational retrospective study. The median follow-up time was 24.0 (21.5–26.5) months. The ORR and DCR were 40% and 73.3%, respectively. The median TTR was 2.4 months and the median DOR was 5.0 months. The median PFS and OS were 7.5 months and 17.0 months, respectively. The most common TRAEs were fever (83.3%), fatigue (73.3%), and nausea (70%). Of all TRAEs, thrombocytopenia and neutropenia were the most frequent severe AE (both 10%). Conclusion The combination of camrelizumab and GEMOX is a potentially efficacious and safe treatment modality for advanced ICC patients. Potential biomarkers are needed to identify patients who might benefit from this treatment option.